2022
DOI: 10.1108/ijhma-12-2021-0134
|View full text |Cite
|
Sign up to set email alerts
|

Safe-haven investments against stock returns in Pakistan: a role of real estate, gold, oil and US dollar

Abstract: Purpose This study aims to compare the safe-haven properties of different asset markets such as gold, dollar, oil and disaggregated real estate sector (house, plot and residential) against equity returns in Pakistan over the monthly period of January 2011–December 2020. Design/methodology/approach The authors use wavelet coherence to encapsulate the overall dependence and correlation of asset classes. Further, the authors also study the potential of diversification at the tail of returns distribution by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In another study, the real estate was analysed along with the dollar and gold regarding equity returns from January 2011 to December 2020, by using the wavelet coherence technique. The study found out weak association in the short run and the co-movement between equity returns and gold significantly affects real estate and oil price (Imran and Ahad, 2022). In Pakistan, housing prices have been significantly affected by the changes in the monetary policy from January 2011 to December 2016, the study further found out that easy monetary policy produces a rise in house prices and vice versa, albeit inflation has a strong impact on the housing prices, on the other hand stock market index did not affect much (Umar et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, the real estate was analysed along with the dollar and gold regarding equity returns from January 2011 to December 2020, by using the wavelet coherence technique. The study found out weak association in the short run and the co-movement between equity returns and gold significantly affects real estate and oil price (Imran and Ahad, 2022). In Pakistan, housing prices have been significantly affected by the changes in the monetary policy from January 2011 to December 2016, the study further found out that easy monetary policy produces a rise in house prices and vice versa, albeit inflation has a strong impact on the housing prices, on the other hand stock market index did not affect much (Umar et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%